2021
DOI: 10.3340/jkns.2020.0127
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Off-Hour Hospital Presentation on Mortality in Different Subtypes of Acute Stroke in Korea : National Emergency Department Information System Data

Abstract: Objective : Several studies have reported inconsistent findings among countries on whether off-hour hospital presentation is associated with worse outcome in patients with acute stroke. However, its association is yet not clear and has not been thoroughly studied in Korea. We assessed nationwide administrative data to verify off-hour effect in different subtypes of acute stroke in Korea. Methods : We respectively analyzed the nationwide administrative data of National Emergency Department Information System in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…One possible explanation is a reduction in the number of personnel, the availability of substitute temporary staff, and a decrease in the availability of intervention resources. 5 15) Furthermore, the cognitive status of surgeons, necessary for making appropriate clinical decisions, is likely to be affected by fatigue during off-hours. 28) Previous studies have suggested that such resource limitations may result in higher mortality.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is a reduction in the number of personnel, the availability of substitute temporary staff, and a decrease in the availability of intervention resources. 5 15) Furthermore, the cognitive status of surgeons, necessary for making appropriate clinical decisions, is likely to be affected by fatigue during off-hours. 28) Previous studies have suggested that such resource limitations may result in higher mortality.…”
Section: Discussionmentioning
confidence: 99%